Development of Interactive E-Quiz with Articulate Storyline: Transformation of Plane and Space Geometry Assessment in Higher Education - Ade Andriani; Izwita Dewi; W.L. Sihombing (STKIP Singkawang, 2025)
This research overcomes the problem of traditional assessments in Plane and Spatial Geometry courses which are often unable to measure students' mathematical spatial abilities effectively. Thus, the aim of this research is to develop and evaluate a computer-based assessment instrument using Articulate Storyline which is designed to improve the quality and efficiency of evaluation in this course. The research methodology follows the ADDIE development model, starting with an analysis of the needs of 2nd semester students of the Mathematics Department, FMIPA, Medan State University (UNIMED), followed by design, development, implementation and evaluation. The research results show that this instrument has a high level of validity and reliability, with the majority of students showing good skills in using digital devices and supporting network access. This instrument also received positive responses from students and lecturers, demonstrating its effectiveness in increasing engagement and understanding of the material. In conclusion, this computer-based instrument succeeded in improving the quality of evaluation, although this research was limited to several chapters and one institution. It is recommended that future research expand the scope of materials and implementation contexts to test the generalizability of results as well as overcome network access barriers, opening opportunities for further innovation in academic assessment.